Delayed Recovery after Nonoperative Treatment of an Avulsion Fracture of the Ischial Tuberosity in an Adolescent Gymnast with a History of Growth Hormone Deficiency: A Case Report - Prashant Meshram; Amar S. Vadhera; Rahul Sachdev; Edward G. McFarland (International Journal of Sports Physical Therapy)
# Introduction